Extracellular Vesicles Released by Human Induced-Pluripotent Stem Cell-Derived Cardiomyocytes Promote Angiogenesis - Dougherty, Julie A. (Front Physiol, 2018)
Although cell survival post-transplantation is very low, emerging evidence using stem cell therapy for myocardial repair points toward a primary role of paracrine signaling mechanisms as the basis for improved cardiac function, decreased fibrosis, and increased angiogenesis. Recent studies have demonstrated that extracellular vesicles (EVs) such as exosomes secreted by stem cells stimulate angiogenesis, provide cytoprotection, and modulate apoptosis. However, the angiogenic potential of EVs secreted from human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CM), a terminally differentiated cell type, has not been elucidated yet. Therefore, the main objective of this study is to isolate, characterize, and evaluate the in vitro angiogenic potential of EVs collected from hiPSC-CM conditioned media. The hiPSC-CM were cultured for 2 weeks and EVs were isolated from cell culture medium. Isolated EVs were characterized by transmission electron microscopy (TEM), nanoparticle tracking analysis, and immunoblotting. Furthermore, the angiogenic potential of these EVs was evaluated by tube formation, wound-healing, and cell-proliferation assays in bovine aortic endothelial cells (BAEC). In addition, gene expression levels of growth factors was evaluated in hiPSC-derived endothelial cells (hiPSC-EC) treated with hiPSC-CM-derived EV (CM-EVs) to assess their role in promoting angiogenesis. TEM imaging of CM-EVs showed a presence of a double-membrane bound structure, which is a characteristic of EV. Nanoparticle tracking analysis further confirmed the size and shape of the secreted particles to be consistent with EVs. Furthermore, EV-specific markers (CD63 and HSP70) were enriched in these particles as illustrated by immunoblotting. Most importantly, BAEC treated with 100 μg/ml of CM-EVs showed significant increases in tube formation, wound closure, and cell proliferation as compared to control (no-EVs). Finally, treatment of hiPSC-EC with CM-EVs induced increased expression of pro-angiogenic growth factors by the endothelial cells. Overall, our results demonstrated that EVs isolated from hiPSC-CM enhance angiogenesis in endothelial cells. This acellular/cell-free approach constitutes a potential translational therapeutic to induce angiogenesis in patients with myocardial infarction.